Tourist arrivals to muslim countries: pre- and post-September 11 - Mat Ghani, Gairuzazmi (Statistical Economic and Social Research and Training Centre for Islamic Countries, 2019)
The incident that occurred on 11 September 2001 changed tourist arrival patterns directly afterward, not only in the United States but also in the Middle East. In the longer run, the negative media portrayal of Islam and Muslim countries after the 9/11 incident also effected tourist travel patterns. This paper examines whether the 9/11 incident affected tourist arrival patterns in Muslim countries using the bilateral tourism flows gravity model. The result indicates that the Muslim country effect was only visible after 2001. Before the September 11 incident, the patterns of tourist arrival between a pair of Muslim and non-Muslim countries were similar.